2020
DOI: 10.1002/jbio.201960033
|View full text |Cite
|
Sign up to set email alerts
|

SERS‐based biosensor for Alzheimer disease evaluation through the fast analysis of human serum

Abstract: Alzheimer disease (AD) is the most common form of dementia in the elderly, progressively affecting the cognitive functions with a complex diagnostic procedure that limits the time for a prompt intervention. In this study we optimized a reliable protocol for the analysis of AD patients and healthy subjects' serum using the Surface Enhanced Raman Spectroscopy (SERS), taking into consideration the effect of different variables on the final spectra, analyzed and compared through multivariate analysis and correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The specific Raman fingerprint was calculated performing the average spectrum of each experimental group and comparing the resultant spectra through subtraction with error dispersion, individuating the significant intensities variations at the ± 0.005 ∆I level (Fig. 2 a–c) 53 . The single spectra classification model was created and trained using the MVA approach, consisting in consecutive PCA and LDA on the created Raman database, using the whole collected spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The specific Raman fingerprint was calculated performing the average spectrum of each experimental group and comparing the resultant spectra through subtraction with error dispersion, individuating the significant intensities variations at the ± 0.005 ∆I level (Fig. 2 a–c) 53 . The single spectra classification model was created and trained using the MVA approach, consisting in consecutive PCA and LDA on the created Raman database, using the whole collected spectra.…”
Section: Methodsmentioning
confidence: 99%
“…lected from the two experimental groups, with accuracy, precision, and specificity of 83%, 86%, and 86%, respectively. On the other hand, the authors found a direct relationship between brain tissue degeneration visualized by magnetic resonance imaging (MRI) and the appearance of a specific biochemical pattern from SERS data in serum collected from AD patients, showing that SERS is a potential label-free tool for monitoring AD progression and rehabilitation treatments in a minimally invasive way [89]. Hybrid bionanomaterials, such as DNA-AuNPs conjugates, provide excellent platforms for chemical and biological applications.…”
Section: Sers Biosensors For the Simultaneous Detection Of Aβ And Taumentioning
confidence: 99%
“…To this end, various SERS‐based biosensing methods are reported for AD biomarker detection. [ 157 ] Yang et al developed Ag nanogap shells (AgNGSs) as SERS active colloidal NPs for the selective and sensitive multiplexed determination of Aβ 1‐42 and Aβ 1‐40 in blood samples of AD patients. [ 158 ] As shown in Figure 6B, SERS‐based bioselective biosensors were designed and fabricated as a “sandwich” structure with AgNGSs and specific Aβ antibody conjugated on the surface of magnetic beads.…”
Section: Nanodiagnostic Approaches For Admentioning
confidence: 99%